Sistem Kehakiman Anak Negeri Sabah dalam konteks pelaksanaan hukuman dan denda adat / Rafidah@Malissa Binti Salleh, Lenny James Matah and Ku Mohd Amir Aizat Ku Yusof - Sallleh, Rafidah@Malissa; James Matah, Lenny; Aizat Ku Yusof, Ku Mohd Amir (Universiti Teknologi MARA, Sabah, 2019)
Sabah is known for its multi-ethnic population. One of the uniqueness of the state is the existence of Native court system in its legal system. The Native Court is responsible to try cases relating to native customs of the Sabah's indigenous people irrespective of their religion. Thus, in Sabah, there are three different judicial systems exist, namely the civil court system, the Syariah court system and the Native Court system. The objective of this paper is to look at the Native Court system, and to discuss the importance of this traditional judicial system to the indigenous communities. Also, the paper will examine the legal sources and the types of customary penalties imposed by the Native Court of Sabah, in particular the customary penalty, which is known as sogit. Sogit is a customary penalty involving a ceremony sacrificing animals, such as buffalo, chicken or pig, followed by a ritual to calm the spirits. In term of jurisdiction, the Native court has jurisdiction to pass customary penalties such as sogit in the event of any breach of the native customary lawsbasedontheNativeCourtsEnactment1992.While the natives of Sabah live in a modern era, the fact is that they are still bound by customs and the native customary penalties.